THE STUDY OF A HAPPY WORKPLACE OF THE ROYAL THAI ARMY NURSING COLLEGE - Chaleoykitti, Saisamorn; Prasitwechakul, Ayuporn; Klinchet, Nuntikarn (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2022)
This study was descriptive research. The objectives of this study were to study happiness among nursing students and personnel at the Royal Thai Army Nursing College (RTANC) and to study guidelines to develop a happy workplace for the RTANC. The sample consisted of 2 groups, including 1) nursing students from the 1st year to the 4th year and practical nursing students, in the academic year 2021, in a total of 476 students, and 2) personnel at the RTANC in the academic year 2021 comprising 46 nursing instructors and 84 supportive personnel (n = 606). Cronbach’s alpha coefficient of Happinometer, a self-administered questionnaire, was .96. Data were analyzed by using descriptive statistics with frequency, percentage, mean and standard deviation. Content analysis was conducted for guidelines to develop a happy workplace for the RTANC. The results showed that the overall happiness was at a very happy level (M = 4.01, SD = .92). The highest averages were happiness in having good family (M = 4.24, SD = 1.09), good health, and good spirit (M = 4.20, SD = 1.01 and M = 4.20, SD = .74, respectively). All of them were at a very happy level. Other aspects were also at a very happy level except for great financial that was only at a happy level (M = 3.70, SD = 1.02). Suggestions for the development of a happy workplace at the RTANC from the participants were good interpersonal relations, environmental development, and living facility management. Teaching and learning about curriculum must be focused on curriculum development, instructors, learners, and activities to relax from studying.